Analysis of Land Use Changes and Land Suitability for Rice Fields in Tanjung Jabung Barat District - Soni Pratomo; Latifa Latifa; Anis Tatik Maryani; Hutwan Syarifuddin (Jurnal Daur Lingkungan, 2022)
Conversion of agricultural land to non-agriculture is an unavoidable phenomenon, therefore efforts are needed to regulate land use. The purpose of this study is to analyze the rate of conversion of paddy fields by identifying patterns and spatial changes in land and the factors that influence it, as well as analyzing the suitability and availability of lowland rice fields and the suitability of existing lowland rice fields with spatial pattern plans. The study used primary data in the form of semi-detailed soil maps, and secondary data in the form of supporting data and reports. The analytical tools used are Geographic Information Systems, and binary logistic regression. Based on the results of the analysis, it shows that the overall pattern of land use change is 26 patterns of change with a total change area of 127,154 ha (25.81 %), where the area of rice fields is reduced by 1,241 ha in the period 2010-2018. The locational rent factor that has the greatest chance of causing rice field conversion is the distance to the center of the kelurahan/village with a negative coefficient (-3.25461631). The most dominant actual land suitability for existing lowland rice is S1 (74.58%) then S3rf (13.86%) and S3r (10.83%), S3e (0.55%). Evaluation of the alignment of the actual land suitability of the existing rice fields with the spatial pattern plan obtained in the aligned category (67.65%) and potentially aligned (28.16%) with the proposed recommendation that existing rice fields can be one of the considerations for sustainable food land allocation by carrying out strict control on the conversion of paddy fields as well as increasing management efforts to obtain more optimal rice production results and as a material for consideration in reviewing the spatial planing in the RTRW.